Macrophage profile and homing into breast milk in response to ongoing respiratory infections in the nursing infant. (May 2020) - Zheng, Yingying; Corrêa-Silva, Simone; de Souza, Eloisa Corrêa; Maria Rodrigues, Regina; da Fonseca, Fernanda A. Macaferri; Gilio, Alfredo Elias; Carneiro-Sampaio, Magda; Palmeira, Patricia
Highlights: Human milk macrophages are more anti-inflammatory compared to blood monocytes. Nursing infant infection increases the anti-inflammatory macrophage profile in milk. Nursing infant infection increases IL-8, IL-6, CCL2 and CX3CL1 in their mothers' milk. These results reinforce the adaptation of the mother's milk to her child's infections. Abstract: Studies have shown that immune components of human milk can be changed during an infection in the nursing infant. Macrophages are abundant in human milk and they are classified into inflammatory (CD16 − ) and noninflammatory (CD16 + ) subsets. This study investigated CD16 + and CD16 − macrophage homing into breast milk in response to ongoing infections in nursing infants. Peripheral blood and mature milk were collected from 33 healthy mothers of nursing infants with respiratory infections (Group I) and from 26 healthy mothers of healthy nursing infants (Group H). Blood and milk total, CD16 − and CD16 + monocyte (Mo)/macrophage (Mφ) subsets, respectively, and CCR2 and CX3CR1 expression and cytokine levels were analyzed by flow cytometry. CCL2 and CX3CL1 were quantified by ELISA and cytokines by flow cytometry in serum and milk. There was an increase of total and CD16 + Mφ, and, also a decrease of CD16- Mφ frequencies in maternal milk from Group I compared to Group H, but absolute numbers analyses showed higher numbers of all subpopulations of milk Mφ in Group I compared to Group H. Higher numbers of CX3CR1 + CD16 + and double-staining of CCR2 and CX3CR1 in both CD16 + and CD16 − cells were observed in milk during infant infection, which weren't observed in the blood. CCR2 expression was hardly found in milk CD16 − Mφ in both groups. CCL2 and CX3CL1 were both higher in milk than in blood from both groups, but Group I showed higher levels of these chemokines in milk than Group H. Breast milk showed higher IL-6 and IL-8 concentrations than serum, and infant infection caused an increase in these cytokines only in milk. Our findings suggest that milk Mφ profiles are different from blood Mo, and the ongoing infection in the nursing infant could change milk Mφ to a more anti-inflammatory profile compared to that in the healthy group, possibly as an additional strategy of infant protection.